(NsTATISTI^ESKAQ TEORIQ TWERDYH I VIDKIH KRISTALLOW (B/s - (NbAZAROW(B, (NiWAN pAWLOWI^s; (NgEWORKQN(B, (N|DWARD wIGENOWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1983)
(NbIBLIOGR(B. 328 (NNAZW(B.s
Keywords: (NtWERDYE KRISTALLYs